Modulation of adult-born neurons in the inflamed hippocampus - Belarbi, Karim; Rosi, Susanna (Frontiers in Cellular Neuroscience, 2013)
Throughout life new neurons are continuously added to the hippocampal circuitry involved with spatial learning and memory. These new cells originate from neural precursors in the subgranular zone of the dentate gyrus, migrate into the granule cell layer and integrate into neural networks encoding spatial and contextual information. This process can be influenced by several environmental and endogenous factors and is modified in different animal models of neurological disorders. Neuroinflammation, as defined by the presence of activated microglia, is a common key factor to the progression of neurological disorders. Analysis of the literature shows that microglial activation impacts not only the production, but also the migration and the recruitment of new neurons. The impact of microglia on adult-born neurons appears much more multifaceted than ever envisioned before, combining both supportive and detrimental effects that are dependent upon the activation phenotype and the factors being released. The development of strategies aimed to change microglia toward states that promote functional neurogenesis could therefore offer novel therapeutic opportunities against neurological disorders associated with cognitive deficits and neuroinflammation. The present review summarizes the current knowledge on how production, distribution and recruitment of new neurons into behaviorally relevant neural networks are modified in the inflamed hippocampus.